The Utilitation of Fish Scale Waste as A Chitosan - Rinto Muhammad Nur; Asy’ari Asy’ari (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Fish scales are fishery waste that can still be utilized because many contain chemical compounds such as organic proteins (41–84%), and the rest are mineral residues and inorganic salts. Fish scales are reported to contain proximate, calcium, and chitin. Chitin can be extracted into chitin by the deasetillation process. Chitosan is a biomaterial that can be used as a food preservative, a pharmaceutical ingredient. This research aims to extract chitin from fish scales and find out the comparison of chitin rendemen in different types of fish. The study was conducted from July to September 2020. Samples of fish scales Upeneus mullocensisi, Lethrinus sp., Caesio chrysozona, and Scarus rivulatus were obtained from the Traditional Market and Morotai Culinary Center. The process of making chitosan is carried out in the FPIK Laboratory of Universitas Pasifik Morotai. The extraction of chitosan from fish scales through three stages is deproteination, demineralization, and deasetilation. The results showed the protein and mineral content of fish scales vary, namely Upeneus mullocensisi (67.83% and 29.84%), Lethrinus sp. (36.80% and 15.99%), Caesio chrysozona (51.84% and 22.99%), and Scarus rivulatus (82.96% and 14.31%). The highest chitosan rendemen in Lethrinus sp. (13.22%), followed by Caesio chrysozona (7.74%), Upeneus mullocensisi (0.80%), and Scarus rivulatus (0.05%). Some chitosan characteristics, such as color, shape, and smell, meet commercial chitosan standards.